Prosedur Implementasi Prinsip-Prinsip Good Corporate Governance Dalam Program Corporate Social Responsibility Pada Perusahaan Daerah PDAM Kabupaten Bantul - Abdurahman, Agus; Pahlevi, Reza Widhar (Universitas Muhammadiyah Yogyakarta, 2018)
The purpose of this research is to know the implementation procedure of good corporate governance (GCG) principles in Corporate Social Responsibility (CSR) program, through the identification of stakeholders, namely commissioners, directors, and stakeholders; investivigasi GCG operational framework, and explore the procedures and implementation of GCG principles in CSR programs. The approach used in this research is qualitative approach, that is triangulation test and objectivity test. The data collection technique used interview technique, where the source of irisis comes from three stakeholders. Further analysis is performed in accordance with triangulation test approach and objectivity test. The results show that 1) Board of commissioners, directors, and stakeholders have their respective roles in the framework of developing the operational framework of GCG in PDAM Bantul. Stakeholders in PDAM Bantul play a role in mutual supervision between one party with other parties so that the company can survive in running Good Corporate Governance (GCG). 2) The design of GCG operational framework implemented by PDAM Bantul can not be separated from the close relationship between stakeholders and Corporate Social Responsibility (CSR). Stakeholders play an important role in order to formulate, develop, and implement CSR programs. In preparing the CSR program that will be implemented by PDAM Bantul, the stakeholders are also strongly supported by the application of GCG principles which are also based on the Deloitte Governance model, making it easier for PDAM Bantul to implement a well-designed CSR program. 3) PDAM Bantul from the point of view using the Deloitte Governance model has been able to manage the nine elements well so that the Good Corporate Governance (GCG) practices of PDAM Bantul well done and moreover well the application of GCG principles, the CSR program designed by PDAM Bantul can Well done.